The Effect of Health Education on Glycemic Control of Patients DM Type 2 in Families with A Family Approach Self Care - Yusuf, Bahtiar; Maryen, Yehud; Yuliati, Yuliati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes mellitus is a chronic metabolic disorder with a global prevalence of 537 million with an age range of 20-79 years, a mortality prevalence of 6.7 million. Diabetes education improves self-management, glycemic control and quality of life. This study aims to determine the effect of diabetes health education on glycemic control. Quasi-experimental research with a one group pre-test and post-test design, the sample was carried out by accidental sampling at the Fakfak Health Center and the Sekban Health Center in June - August 2024 as many 52 respondents. The instrument used, the Diabetes Self-Management Questionnaire (DSMQ), has undergone robust validity and reliability testing, showing a Cronbach's alpha coefficient of 0.908. The Diabetes Knowledge Questionnaire (DKQ) achieved a Cronbach's alpha of 0.937, indicating high internal consistency. This confirms that both questionnaires are valid and reliable and can be used in this study. Analysis with statistical pairet sample test with significance α ≤0.05. Results: Female gender 44 people, average age 53 years, housewife occupation 69.2%, average duration of diabetes >5 years, regular exercise 19%, irregular 81%, diabetes diet 96%, regular medication consumption 71.2%, history of wounds 17.3%, walking barefoot 34.6%, getting DM information 92.3%, average BMI 26.2, hypertension 65.4%. GDS value <200mg/dl before education was 19 people (36.5%) after education 27 people (51.9%). While GDS>200mg/dl before education was 33 people (63.5%), after education 25 people (48%). The average score before and after education was 222mg/dl and 193mg/dl. The p value is 0.001. Conclusion: diabetes health education increases knowledge and controls glucose with a self-care approach.